Antimicrobial compounds from intracellular and extracellular secondary metabolites of Actinobacteria InaCC A759 - Maya Dian Rakhmawatie; Mustofa Mustofa; Puspita Lisdiyanti; Tri Wibawa; Kanti Ratnaningrum; Muhammad Mucharom Chairul Umam; Muhammad Hasan Alfi; Listya Chariri (Indonesian Journal of Biotechnology, 2024)
The World Health Organization (WHO) has determined a list of pathogens that require the development of new antimicrobials due to resistance problems; these include Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus. In addition, Mycobacterium smegmatis has been used for antimycobacterial discovery to address the increasing burden of tuberculosis. In this study, optimization of antimicrobial activity, secondary metabolite profiling, and strain identification was conducted on Actinobacteria InaCC A759. Intracellular and extracellular extracts of Actinobacteria InaCC A759 were found to have different antimicrobial activities. The minimum inhibitory concentration (MIC) values of the extract to inhibit the growth of M. smegmatis, E. coli, and P. aeruginosa were 50, 25, and 100 µg/mL (intracellular), and 25, 25, and 100 µg/mL (extracellular), respectively. However, neither extract was able to inhibit the growth of S. aureus. Metabolite profiling using High resolution‐mass spectrometry (HR‐MS) resulted in differences in the major compound between the two extracts of Actinobacteria InaCC A759, namely n‐acetyltyramine (C10H13NO2/179.0945) (24.24%) (intracellular) and palmitic acid (C16H32O2/273.27034) (86.92%) (extracellular). Based on molecular analysis of the 16S rRNA gene, Actinobacteria InaCC A759 is identical to the Streptomyces olivaceus strain FoRh46. The antimicrobial activity and secondary metabolites profiles of Streptomyces olivaceus InaCC A759 have not been previously reported.